Association of chromosome 2q36.1–36.3 and autosomal dominant transmission in ankylosing spondylitis: results of genetic studies across generations of Han Chinese families. Issue 10 (4th May 2009) - Gu, J; Huang, J; Li, C; Zhao, L; Huang, F; Liao, Z; Li, T; Wei, Q; Lin, Z; Pan, Y; Huang, J; Wang, X; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic, potentially crippling, spondyloarthropathy with strong genetic components affecting approximately 0.3% of the population. Its exact genetic mechanism and mode of transmission, however, remains obscure. Methods and results: The authors conducted a genome wide scan on 75 individuals across multiple generations of three Han Chinese families affected with AS. Segregation analysis and pedigree investigation suggested an autosomal dominant inheritance. Pairwise logarithm of odds (LOD) scores were calculated using LINKAGE package for the obtained genotypes. High resolution mapping was then performed based on markers with significant LOD scores. To minimise the number of crossovers in each family, haplotype were constructed and assigned. Two of the pedigrees shared one candidate region for AS on 2q36.1–2q36.3 spanning 6-cM (maximum heterogeneity LOD score of 12.41 at marker D2S2228), while the other showed strong linkage to the HLA-B region. Conclusions: This is the first report which proposes one of the new genetic models of autosomal dominant transmission in AS. The breakthrough in the identification of linkage to chromosome 2q36.1–2q36.3 and the HLA-B region highlights the future potential of more comprehensive genetic studies of determinants of disease risk.